The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1038/s41598-017-08962-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel in vitro potency assay of antisera against Thai Naja kaouthia based on nicotinic acetylcholine receptor binding

Abstract: Snake envenomation is an important medical problem. One of the hurdles in antivenom development is the in vivo assay of antivenom potency which is expensive, gives variable results and kills many animals. We report a novel in vitro assay involving the specific binding of the postsynaptic neurotoxins (PSNTs) of elapid snakes with purified Torpedo californica nicotinic acetylcholine receptor (nAChR). The potency of an antivenom is determined by its antibody ability to bind and neutralize the PSNT, thus preventin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…The optimal concentrations of these four reagents used in the in vitro potency assay were described in a previous study 13 . The optimal concentration of NK3 for coating the plates was 15 µg/ml, and 0.707 µg/ml of nAChR for binding to the NK3 coated plate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The optimal concentrations of these four reagents used in the in vitro potency assay were described in a previous study 13 . The optimal concentration of NK3 for coating the plates was 15 µg/ml, and 0.707 µg/ml of nAChR for binding to the NK3 coated plate.…”
Section: Resultsmentioning
confidence: 99%
“…naja (Sri Lanka), a good correlation between the in vitro nAChR-PSNT binding activity and the in vivo murine lethality neutralization activity was obtained. The reason behind this observation could be that the presence of a large amount of cytotoxins in the venom did not affect the results of the in vitro nAChR - PSNT binding assay since the assay has been shown to be specific to PSNT and not to cytotoxins 13 . Furthermore, the results suggested that death is mainly the result of the α-neurotoxins since α-neurotoxins are about 10 times more toxic, with an LD 50 of ca .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations